33.1k views
5 votes
(Algebra 1 ~ High School)

The table shows the solution to the equation |2x − 3| − 1 = 2:
Step 1 |2x − 3| = 2 + 1
Step 2 |2x − 3| = 3
Step 3 2x − 3 = 3 or 2x + 3 = 3
Step 4 2x = 6 or 2x = 0
Step 5 x = 3 or x = 0

Which is the first incorrect step?
a. Step 1
b. Step 3
c. Step 5
d. Solution is correct

2 Answers

2 votes

Step 2 I believe. You are supposed to find the absolute value before adding

User Jsears
by
5.3k points
4 votes
The solution is step 3. In step three they gave themselves two answers which is wrong. The lines mean absolute value, which means that it should be +3 not -3.
User Jtmnt
by
5.8k points